Why we need arts education : revealing the common good: making theory and practice work better - Cannatella, Howard (SensePublishers, 2015)
This is a book that will be of interest to those who teach, know, care, theorise, administer, set policies and discuss the arts in education. Each chapter in this book makes various references to actual arts teaching practices. Teaching and learning examples figure prominently. Concrete teaching incidents are covered throughout the book. Various actual classroom teaching situations are given. Highlighted, at particular points, are arts teaching practices that demonstrate how the arts drive up standards in education generally and why teaching expertise in the arts can be seen as central to this. Teaching practices and theories in the arts overlap in applied ways. Current teaching and curriculum issues are debated. Teaching explanations expressing the actions, character and skills of an art, the knowledge claims, the truth relationships, ideas and conceptions in student focused contingent ways are discussed. Explored are learner-like, student-teacher dialogues, everyday shared common experiences of art, and the reverent pleasures and insights that correspondingly relate to how things are worked, felt and examined by students. Familiar, ordinary, cherished, touching, sensitive and dignified comprehensions are portrayed. In capacity strengthening ways, the book attends to the elevated, consensual, continuous, broad, united, narrow, enlarged, diverse, open, freed, lively, inventive, imaginative, deeper and richer horizons that exemplify how the arts in education, as a common good, contribute to society. This text argues persuasively why we should be teaching arts education more comprehensively in a public system of education and how we should be doing it.